Fossil Melandryidae (Coleoptera: Tenebrionoidea) from Eocene Baltic amber of the Sambian peninsula: new genus, six new species, new records and key to described taxa - Alekseev, Vitalii Igorevich; Bukejs, Andris (Zootaxa, 2021)
Six new extinct representatives of the family Melandryidae, namely Electroxylita chronographica gen. et sp. nov., Madelinia capillata sp. nov., Microscapha kugelanni sp. nov., Phloiotrya inmarinata sp. nov., Symphora pollocki sp. nov., and S. glaesonauta sp. nov. are described from inclusions in Eocene Baltic amber. Twenty-eight additional fossil specimens of melandryid beetles belonging to ten species are reported. A list of Melandryidae described from Baltic amber is compiled and an identification key is provided.